EVALUASI KESESUAIAN LAHAN UNTUK TANAMAN KACANG TANAH DI SUB DAS PANASEN KABUPATEN MINAHASA - Sukmawati Misi; Murdiyanto Murdiyanto; Grace F.E Suoth (Jurusan Pendidikan Geografi Universitas Negeri Manado, 2021)
Peanut is a plant that has an important role in land and has a high selling value. Therefore it is necessary to take appropriate steps to develop peanut cultivation in the Panasen Sub-watershed by knowing the level of land suitability. The problems faced by the community are 1) lack of interest in the community to plant peanuts, 2) land-use change from agricultural land to lodging land 3) land evaluation has never been carried out for peanut plants in the area. The study used a land unit approach supported by soil analysis, plant growth requirements, and matching. The results showed that the research area was classified as suitable for peanut plants with a suitability class S2 (quite suitable) with a total of 4 land units, namely S2rfns (945.41 ha), S2sn (1675.15 ha), S2srn (938.05 ha), S2sn (13.45 ha) and class suitability of S3 (according to marginal) with 2 land units, namely S3s (12.95 ha), S3s (15.67 ha). The limiting factors for suitability class S2 are root media (r), nutrient retention (f), nutrient availability (n) and terrain (s). The limiting factor for suitability class S3 is the field (s). The limiting factor for N1 land suitability is nutrient availability (n), root media (r) and terrain (s). The limiting factors for conformity class N2 are the field (s) and the rooting medium (r).